The impact of ethnicity and gender on agreement of severe allergy history between inpatient and outpatient electronic medical records - Reinhart K; Corbo T; Ewen E; White CM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Objective: To evaluate the rate of allergy documentation during inpatient admissions and determine if discrepancies exist between ethnicities and English proficiency, genders, and by medication classes.Methods: Patients at an outpatient clinic with severe medication allergies documented in their electronic medical record were identified. Inpatient hospital admissions following the date this allergy was documented were reviewed and the presence or absence of this documentation in the inpatient electronic medical record was noted. An overall rate of successful documentation of allergies was calculated by dividing the number of admissions where the allergy was entered into by the total number of admissions where the opportunity to enter the allergy existed. Each patients ethnicity, gender, and the class of medication to which they were allergic to, was also recorded to determine if difference exist within each demographic. Results: Overall, allergy information was successfully entered in 84.6% of 246 hospital admissions. This rate was significantly lower (37.5%) among patients whose ethnicity groups, on average, have lower rates of English fluency. There was no significant difference between genders. Allergies to cephalosporins were less likely to be entered (44.4%).Conclusion: Patients who are not proficient in speaking English may be at an increased risk of experiencing an adverse drug reaction as their severe allergies are less likely to be documented during a hospital admission.